The mechanisms crosstalk and therapeutic opportunities between ferroptosis and ovary diseases - Yao, Ying; Wang, Bin; Jiang, Yanbiao; Guo, Hong; Li, Yulan (Frontiers in Endocrinology, 2023)
Ferroptosis, a form of regulated cell death, was first defined in 2012. Ferroptosis mainly involves iron-driven lipid peroxidation damage of cells. This process is regulated by iron homeostasis, redox balance, lipid metabolism,glutathione metabolism, and various disease signaling pathways. Iron is one of the key mineral elements that regulate the physiological function of women and the development of ovarian tumors. Occurrence of Ferroptosis has some hidden dangers and advantages in ovary diseases. Some scholars have shown that ferroptosis of ovarian granulosa cells (GC) promotes the development of ovarian dysfunction and polycystic ovary syndrome (PCOS).Interestingly, drug-resistant ovarian cancer cells are very sensitive to ferroptosis, suggesting that pharmacological positive and negative regulation of ferroptosis has great potential in the treatment of benign ovarian diseases and ovarian cancer. This article aimed to assess how ferroptosis occurs and the factors controlling ferroptosis. Moreover, we summarize how ferroptosis can be used to predict, diagnose and target treatment ovary disease. Meanwhile, we also evaluated the the different phenomena of Ferroptosis in ovarian diseases. It aims to provide new directions for the research and prevention of female reproductive diseases.Ferroptosis was originally defined as iron-mediated lipid peroxidation damage, which is closely related to the physiological and pathological mechanisms of the ovary. Although iron is a micromineral component, it is essential in various biological processes, including oxygen transport, energy metabolism, cell growth, and differentiation. Women have some unique physiological characteristics, such as excessive menstrual volume, increased maternal blood volume during pregnancy, fetal development, and postpartum blood loss. Therefore, adult women usually need more iron than men (1). However, iron is a ' double-edged sword ' and thus should be carefully used while taking measures to prevent iron deficiency. Iron overload can increase unstable iron content in the